(untitled) (Ustozlar uchun, 2026)
Drawing on established international conventions and practices, the article highlights how these documents underpin legal accountability and protect stakeholders in cross-border shipments. The conclusion summarizes the findings and emphasizes the evolving role of digital documentation in modern trade. Aimed at bachelor’s-level readers, this piece underscores the foundational knowledge needed for understanding logistics and international business law, supported by references to key sources in the field.This article explores the essential documents involved in international cargo transportation and their critical legal roles in facilitating global trade. It begins with an introduction to the importance of documentation in ensuring smooth logistics operations, compliance with international regulations, and risk mitigation. The first main part provides an overview of key document types, categorized into transport, commercial, and regulatory documents, with explanations of their purposes and contents. The second main part delves into the legal significance, including their functions as contracts, evidence of ownership, tools for customs clearance, and mechanisms for dispute resolution.